TRANSMISSION MECHANISM OF MONETARY POLICY IN TERMS OF VIETNAM - The Dong Phung (Статистика и экономика)
In order to conduct an effective monetary policy, the Central bank should have a clear understanding of the mechanism of the money transfer and the importance of different transmission channels, and the impact of these transmission channels on the sectors of the economy, especially on the manufacturing sector.